Government Policies for the Natural Resource Management of Minerals and Coal Based on Social Welfare - Absori Absori; Aullia Vivi Yulianingrum; Rahmatullah Ayu Hasmiati; Arief Budiono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
This research aims to describe the natural resources management policies in the mineral and coal sectors. The description is based on the social welfare value contained in Law No. 3 of 2020 concerning Amendment of Law No. 4 of 2009 concerning Mineral and Coal Mining, as well as Law No. 11 of 2020 concerning Employment and Labour Law. This research employed a normative judicial method based on law regulations that are conceptualized as principles or norms and have evolved into proper human behavior standards. Secondary data were employed by exploring literature correlated with the mineral and coal mining management law and analyzed using juridical-qualitative techniques. Subsequently, the research indicated that the Indonesian government policy in the Mineral and Coal, alongside Omnibus Laws, are unable to accommodate social welfare values and support only profit-oriented businesspersons. This research is expected to proffer suggestions for the central or regional government to make regulations prior to the social welfare principle.